War, peace and international relations : an introduction to strategic history - Gray, Colin S. (Abingdon, UK : New York : Routledge, 2011)
"This new edition of Colin Gray's textbook explores the theory and practice of war and peace in modern historical context. War, Peace and International Relations serves as an excellent introduction to the international history of the past two hundred years, showing how those two centuries were shaped and reshaped extensively by war. This book takes a broad view of what was relevant to the causes, courses, and consequences of wars. The second edition has been thoroughly revised and updated, with new material on colonial warfare, the American Revolution and technology and warfare. This textbook is an invaluable resource for upper-level students of strategic studies, security studies, war studies, international relations and international history"--
"'The author's discussions and clarity of thought and expression make this work ideal as a textbook for introducing civilian students and prospective military officers of the various military academies to the subject.' - Parameters War, Peace and International Relations provides an introduction to the strategic history of the past two centuries, showing how those 200 years were shaped and reshaped extensively by war. The book takes a broad view of what was relevant to the causes, courses, and consequences of wars. Written by leading strategist Professor Colin Gray, the book provides students with a good grounding in the contribution of war to the development of the modern world, from the pre-industrial era to the age of international terrorism and smart weapons. This second edition has been thoroughly revised and updated: - It is the first one-volume strategic history textbook on the market; - It covers all the major wars of the past two centuries; - It is up to date and comprehensive, including new chapters on colonial warfare, the American Civil War, and technology and warfare. This textbook will be essential reading for students of strategic studies, security studies, war studies, international relations and international history"--
Strategic history, 1800-2025 : themes and contexts -- Carl von Clausewitz and the theory of war -- From limited war to national war : the French Revolution and the Napoleonic way of war -- The nineteenth century, I : a strategic view -- The nineteenth century, II : technology, warfare, and international order -- The Great War and the invention of modern warfare, 1914-18 -- The twenty-year armistice, 1919-1939 -- The Second World War in Europe, I : the structure and course of total war -- The Second World War in Europe, II : understanding the war -- The Second World War in Asia-Pacific, I : politics -- The Second World War in Asia-Pacific, II : strategy -- The Cold War, I : politics and ideology -- The Cold War, II : the nuclear revolution -- War and peace after the Cold War : the interwar decade -- 9/11 and the age of terror.
Includes bibliographical references (p. 351-364) and index.
Keywords: War; Military policy; Strategy; International relations; Military history, Modern -- 19th century; Military history, Modern -- 20th century; HISTORY / Military / Strategy; POLITICAL SCIENCE / International Relations / General; HISTORY / Military / General